Neonatal uroperitonium in female equine: Case report - Scarpioni, Lorena Bueno; Lima, Caio Abílio Silva; Celotti, Gustavo (Seven Editora, 2024)
Uroperitonium is defined by the accumulation of urine in the abdominal cavity, mostly being generated by the rupture of the urinary gallbladder, affecting young foals.  The clinical symptoms of the disease include apathy, dyspnea, tachypnea, abdominal distension, discomfort and can cause death due to imbalance due to intense uremia.  The diagnosis is made through complementary tests, together with the clinic. Complementary tests include abdominal ultrasound and laboratory tests, such as: blood count, biochemistry, analysis of abdominal fluid and urinalysis. The prognosis is poor and depends on the clinical evolution and degree of contamination. The objective of this study is to report a case of uroperitonium in a female neonate, received at the Unifeob Veterinary Center, presenting dyspnea, hyperthermia, apathy and abdominal discomfort.  Complementary tests were of paramount importance for the final diagnosis. Due to the time of evolution associated with the severe degree of contamination, the patient died before the surgical intervention.  DOI:https://doi.org/10.56238/sevened2024.018-044